Never cross a picket line : the story of 500 sacked Liverpool dockers. (Liverpool : Anteus Graphics, 1996)
Bibliotheek François Vercammen
International Conference gehouden in Liverpool van 17 tot 23 februari 1996
Engels
Brochure